Rancang Bangun Virtual reality Tour Pusat Perbelanjaan Modern Berbasis Web - Julianto, Indri Tri; Rustandy, Sandy (Institut Teknologi Garut, 2025)
Garut has nine modern shopping centers that are the main destinations for local residents and visiting tourists. The modern shopping center industry has a significant role in improving the economy and welfare, especially in Garut Regency. Where now virtual reality can complement social media as a source of information. With the development of virtual reality (VR) technology to support modern shopping centers. The purpose of this study is to design, build and implement a web-based virtual reality tour of modern shopping centers using the MDLC method for information media for visitors. The methodology used in this research is the Multimedia Development Life Cycle method consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. The results of this study are the Design of a Web-Based Virtual Reality Tour of Modern Shopping Centers. displays 3600 panoramic images, hotspot features, sound features, videos, and there are google map and chatbot features. The testing method used in this study is using Beta testing obtained a score of 3.98 percent stating that the Ciplaz VR Tour web is feasible to use.